Analisis Finansial Usahatani Tomat Di Desa Tumaratas Dua Kecamatan Langowan Barat Kabupaten Minahasa - Mentang, Melifan; Lumingkewas, Jelly Ribka Danaly; Lolowang, Tommy Fredy (Sam Ratulangi University, 2024)
This research aims to find out whether tomato farming in Tumaratas Dua Village, West Langowan District, Minahasa Regency is financially profitable. The sampling method was carried out by purposive sampling of farmers who harvested in the period June to September 2022. The number of samples taken in this research was 30 respondents. Determining the number of samples in this research was carried out using the Quota Sampling method. The data analysis method is carried out using a quantitative descriptive method by calculating costs, income, income, r/c ratio, break event point (BEP) and sensitivity analysis. Based on the results of financial calculations for tomato farming, it is known that the total production costs are IDR17.343.239/farmer amounting to IDR69.449.803/Ha income of IDR44.811.833/farmer amounting to IDR179.445.893/Ha and income of IDR62.150.628/farmer of IDR248.877.899/Ha in one planting season. The results of the feasibility analysis of tomato farming show an R/C Ratio value of 2.6. This shows that every IDR1 spent by farmers provides a profit of IDR2,6 and well worth the effort. The BEP price value shows the breakeven point at IDR2.139/kg and production BEP shows a breakeven point of 997kg. The total production of tomatoes in this study was 32,465kg/ha and the selling value of tomatoes in this study was IDR5.527/kg. The results of the sensitivity analysis in scenarios I and II show that the R/C ratio is positive >1 and is worth pursuing. The results of the sensitivity analysis for scenario I to a cost increase of 42.63% show an R/C Ratio value of 1.8. The results of the sensitivity analysis of scenario II to a 49% reduction in selling prices show an R/C ratio of 1.3.